The interior of the earth - Bott, Martin Harold Phillips 1926- (London Edward Arnold, 1971)
Textbook on solid-earth geophysics;aims at an integrated description of modern knowledge and theories about the interior of the earth.
Bibliography: p. 289-302.
Keywords: Earth (Planet) -- Internal structure; Earth (Planet) -- Crust; Earth (Planet) -- Mantle